A LABORATORY STUDY ON USE OF SCREW-TYPE FRICTION BOLTS AS NEW SOFT ROCK STABILIZERS - KOMURLU, Eren (GeoScience Engineering, 2024)
In this study, load bearing capacities of screw bolts as a new friction bolt type was investigated carrying out a series of laboratory studies. New screw-type friction bolts with sharp threads were inserted into holes drilled in various soft rocks by applying rotation. Screw bolts and split sets inserted in different soft rock types were investigated to comparatively evaluate their load bearing capacity values. According to the results obtained from this study, new screw bolts were found to supply better load bearing capacity values than those of the split sets. Although the split sets are quite popular friction bolts used in rock engineering, they have significant disadvantages resulting from their poor anchorage performances in soft rocks. By making grooves on drill hole contact surfaces, increased coefficient of friction and load bearing capacity values can be supplied by new screw bolts which were found to be advantageous for using in soft rocks.